Circular economy of Construction and Demolition Waste: A Case Study of Colombia (2022)
ABSTRACT: This paper presents the results of research into construction and demolition (C&D) waste in Colombia. The data and analyses are shown in a local and Latin American context. As the situation in Colombia is quite similar to that in many developing countries worldwide, this research and its findings are potentially applicable to similar economies. Several factors were calculated and compared in order to evaluate which best fit the data from Colombia. We also included an experimental characterization and analysis of several key types of C&D waste from important infrastructure projects in Colombia, specifically by using the X-ray diffraction and scanning electron microscopy techniques. For the quantification of CDW, a calculation was performed based on the area and four factors of volume and density, followed by an econometric analysis of the detailed information using the Hodrick–Prescott filter, which revealed the CDW trends. Our results revealed that there are limitations regarding the availability of information and effective treatments for this waste, as well as shortcomings in education and other issues, not only for Colombia but also for other countries in Latin America.